Die Bistümer der Kirchenprovinz Köln. Das Bistum Münster 11. Die Zisterzienserabtei Marienfeld - Kohl, Wilhelm 1913-2014 (Germania sacra, 2010)
The Cistercian Abbey of Marienfeld, founded by a group of Westphalian noblemen in 1185, is considered to be one of the most important monasteries of the Diocese of Münster. Due to the active support of Bishop Hermann II, it soon reached its zenith. Following the well-established pattern of Germania Sacra, Wilhelm Kohl, renowned expert of the history of the diocese of Münster, provides an outline of the history, constitution, spiritual and religious life, the history of the property and in particular a list of persons of the abbey from its foundation to its dissolution in 1803. Die Zisterzienserabtei Marienfeld, gegründet 1185 von einer Gruppe westfälischer Adliger, zählt zu den bedeutendsten Klöstern der Diözese Münster. Mit tatkräftiger Unterstützung des Münsteraner Bischofs Hermann II. erreichte sie bald ihre Blütezeit. Nach dem bewährten Schema der Germania Sacra skizziert der renommierte Kenner der Geschichte des Bistums Münster, Wilhelm Kohl, die Geschichte, die Verfassung, das geistige und religiöse Leben, die Besitzgeschichte und vor allem das Personal der Abtei von ihrer Gründung bis zur Aufhebung 1803.